Penerapan Sistem Informasi Persediaan Stok Umbi Porang Berbasis Android Sebagai Upaya Peningkatan Kinerja Pelaporan - Aulia, Syifa Durrotul Fuadah; Artika, Selfi (Fakultas Teknik Universitas Hamzanwadi, 2024)
Porang tubers are a type of food plant in which there are carbohydrates and proteins as a source of human energy. Indonesia is an agrarian country with a large agricultural area, so most of the population make a living as farmers. PT. Barokah Rizky Abadi is one of the companies engaged in agriculture, especially the sale of tubers that focuses on selling porang tubers. Stock inventory system at PT. Barokah Rizky Abadi uses manual recording of tuber stocks, namely from bookkeeping, and has not been equipped with system device information to manage the inventory of porang tubers, this is considered less effective and less accurate. From these problems, an Android-based application was made that can help in doing agency work, especially the warehousing department. The method used is a qualitative method with a Research and Development (R&D) strategy with flowcharts, DFD, and ERD so that the management of information systems is more systematic. The result of this study is the Android Application-Based Porang Tuber Stock Inventory Information System at PT. Barokah Rizky Abadi